Primary aldosteronism long-term outcome: Medical versus surgical therapy. (October 2019) - Schneider, Holger; Williams, Tracy A.; Heinrich, Daniel A.; Lechner, Benjamin; Reincke, Martin
Abstract: Primary aldosteronism is now established as the most frequent form of endocrine hypertension. Beside the long-term effects of hypertension itself, mineralocorticoid and glucocorticoid excess pose additional, independent risks of end-stage renal disease and cardiovascular morbidity and mortality. These increased risks can be mitigated or reversed by specific treatments to directly target the underlying cause; even more so, targeted therapy of mineralocorticoid excess has been shown to carry prognostic superiority exceeding optimal blood pressure control alone and should therefore always be always preferred. Patient management is achieved with medical or surgical therapy. The choice of treatment modality depends on the underlying subtype, the accompanying medical co-conditions, patient preferences, and local resources. In this review, we summarize the long-term outcomes of both treatments in terms of blood pressure control, correction of hypokalemia and renin suppression, need for residual antihypertensive medication, attenuation of mineralocorticoid-associated end-organ damage, and overall survival. The goal is to provide clinicians with outcome measures that can be used to tailor the anticipated benefit of an individualized treatment strategy to the medical needs of a given patient.